Reconstruction of Land Exertion for Investment - Sumardi, Juajir (Amsir Law Journal, 2021)
This study aims to determine the basis of welfare, so the nature of investment in land is placed in the basic values ​​of Pancasila and the 1945 Constitution. The type of research used is normative legal research using a statutory approach. The results show that the concept of diversion through the principle of restorative justice for criminal acts against property has actually been practiced by indigenous peoples in Indonesia since ancient times and is still practiced today, but in the Indonesian legal system or the criminal justice system has not been explicitly regulated in statute form. The use, application and regulation are still at the level of discretion in each law enforcement agency in accordance with the internal rules that bind the respective law enforcement agencies. For this reason, to implement the values ​​contained in Pancasila and the mandate of the state constitution, economic law in the investment sector must be directed at encouraging balanced economic growth, prosperity, and equal distribution of opportunities. In this regard, the obligation to have social and environmental responsibility must be implemented in any investment activity that uses the land as a production factor by giving local governments the role of supervising the implementation level.